2009
DOI: 10.1007/s00455-008-9206-8
|View full text |Cite
|
Sign up to set email alerts
|

Pseudodysphagia Due to Omohyoid Muscle Syndrome

Abstract: Omohyoid muscle syndrome (OMS) is a rare clinical condition that has the pathognomonic feature of the appearance of a lateral neck mass when swallowing due to dysfunction of the omohyoid muscle (OH). We present two cases of typical OMS with electrophysiologic and dynamic imaging studies. The study results indicate that OMS is caused mainly by the loosening of the fascial attachment to the intermediate tendon of the OH. The characteristic clinical features and pathomechanism underlying OMS are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…We suspect that patients with sternohyoid syndrome demonstrate symptoms similar to omohyoid syndrome. Dynamic CT scan and realtime ultrasonography also provide useful information about strap muscles [8,13,15,16]. CT scan showed no abnormal finding of the sternohyoid and omohyoid muscles, which indicates that CT and ultrasound cannot be definite diagnostic tools of sternohyoid or omohyoid syndromes.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…We suspect that patients with sternohyoid syndrome demonstrate symptoms similar to omohyoid syndrome. Dynamic CT scan and realtime ultrasonography also provide useful information about strap muscles [8,13,15,16]. CT scan showed no abnormal finding of the sternohyoid and omohyoid muscles, which indicates that CT and ultrasound cannot be definite diagnostic tools of sternohyoid or omohyoid syndromes.…”
Section: Discussionmentioning
confidence: 92%
“…CT scan showed no abnormal finding of the sternohyoid and omohyoid muscles, which indicates that CT and ultrasound cannot be definite diagnostic tools of sternohyoid or omohyoid syndromes. Kim et al also revealed that needle electromyography showed no abnormal findings [15].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In OMS patients ( Figure 1B), the most important pathology change is loosening of the IT tendon sheath (2). After that, the OM becomes shortened and fibrosis occurs because of atrophy of disuse and degeneration.…”
Section: Introductionmentioning
confidence: 99%